ANALISIS KESIAPAN MITIGASI NON STRUKTURAL WARGA TERHADAP PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN KAWASAN PERMUKIMAN PADAT PENDUDUK (Studi Kasus di RW 16 Kelurahan Kayu Putih, Kecamatan Pulogadung, Kotamadya Jakarta Timur) - Hamas Musyaddad Abdul Aziz; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
One of the examples of disasters that frequently occurred in Indonesia, especially in the big cities in Indonesia are fires densely populated settlements. No exception in Jakarta as the capital city of Indonesia, a city growing in the center of this government annually increasing number of residents and the migrant significantly. One of the initial steps to address the fire problem in congested with preparing the readiness of citizens to anticipate before the occurrence of non-structural mitigation of fires as a means of fire prevention and control in congested. The purpose of this study was to know and analyze the non-structural mitigation readiness of citizens to fire prevention and control densely populated residential areas in the village of Kayu Putih, District Pulogadung, East Jakarta. This research uses descriptive qualitative approach. The samples in this study using purposive sampling. This study takes the key informants as many as eight people and informants triangulation four people. The results showed the knowledge and attitudes of citizens regarding fire prevention and suppression densely populated settlements of all informants know it very well, the environmental conditions in RW 16 Kayu Putih Village including densely populated settlements and slums so relatively vulnerable to a potential fire hazard, Dissemination SKKL new limited appeal, training Balakar've never been there but there is no repetition of material, the Budget funds for fire prevention and suppression in the settlements is indispensable but can not be felt by residents and is now better allocated for the procurement of fire extinguishers, Regarding the role of the Balakar his role is still evident , All the key informants had warned not to do things that can cause a fire in the family, and there is no form of direct supervision of RT / RW / village on fire. Factors - factors that support non-structural mitigation readiness of citizens to fire prevention and control densely